Cell wall modifications lead to cultivar differences in apple (Malus domestica) fruit mealiness - Ayu Nurlaila Indah; Shigeki Moriya; Tomoya Ohta; Rani Agustina Wulandari; Panjisakti Basunanda; Hideki Murayama (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2022)
Recently, four quantitative trait loci linked to flesh mealiness in apples were identified, with one associated with the MdPG1 allele. Hence, this study analyzed cell wall changes in two mealy (Orin and Akane) and three non-mealy (Kiou, Kitaro, Fuji) apple cultivars during ripening. The fruits were harvested for each cultivar at optimum maturity and stored at 20°C for 20 days. The flesh firmness of ‘Kitaro’ and ‘Fuji’ fruit did not change strikingly over the 20 days, whereas that of the other three cultivars, especially ‘Akane’ and ‘Orin’, gradually decreased during ripening. Between the two cultivars with a mealy texture, ‘Akane’ fruit produced extremely low levels of ethylene, whereas ‘Orin’ fruit produced high levels. The water-soluble polyuronide (WSP) contents of ‘Kiou’ and ‘Fuji’ fruit did not change clearly. In contrast, the WSP contents of the other three cultivars, especially ‘Akane’ and ‘Orin’, increased during ripening. In ‘Kiou’, ‘Kitaro’, and ‘Fuji’ fruit, the molecular-mass distributions of WSPs did not change during ripening. Conversely, the molecular-mass distribution of WSPs in ‘Akane’ and ‘Orin’ fruit exhibited downshifts during ripening. These results indicate that solubilization and depolymerization of pectic polyuronides occur during ripening in mealy ‘Akane’ and ‘Orin’ fruit, and that ethylene may not be involved in these changes.